STEM Teacher Professional Learning Through Immersive STEM Learning Placements in Industry: a Systematic Literature Review - Hurley, Mairéad (My University, 2023)
Over the past two decades, there has been an increased focus on designing STEM learning experiences for primary and second-level students. We posit that for teachers to design rich learning experiences for their students, they must first have the opportunity to develop their own STEM knowledge and competences, either during their pre-service teacher education or as part of their professional learning as in-service teachers. This systematic review of literature examines programmes which offer either pre-service or in-service teachers immersive learning experiences through placements in STEM roles in business or industry. A total of nine papers were identified in this review, featuring three unique programmes—one in the UK for pre-service teachers, and two in the USA involving in-service teachers. The findings indicate a variation in motivation and structures across the three programmes. The influence on teachers’ personal and professional development, and their intentions to change their classroom practices or behaviours to incorporate more ‘real-world’ contexts into their STEM learning activities, inspired by their experiences in industry, is discussed. This study presents recommendations for the design and implementation of immersive learning placements in industry to support STEM teacher professional learning, as well as suggestions for further studies to examine the influence on their classroom practice.
PUBLISHED
Keywords: STEM education; Industry placements; Pre-service education; Professional learning; Professional development; Initial Teacher Education; Science Education; Teacher Education